2016
DOI: 10.3390/toxins8060162
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Dietary Phytoestrogens on the Regulation of Epithelial-Mesenchymal Transition in Diverse Cancer Metastasis

Abstract: Epithelial-mesenchymal transition (EMT) plays a key role in tumor progression. The cells undergoing EMT upregulate the expression of cell motility-related proteins and show enhanced migration and invasion. The hallmarks of EMT in cancer cells include changed cell morphology and increased metastatic capabilities in cell migration and invasion. Therefore, prevention of EMT is an important tool for the inhibition of tumor metastasis. A novel preventive therapy is needed, such as treatment of natural dietary subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 158 publications
(161 reference statements)
3
38
0
1
Order By: Relevance
“…For cell cycle, the early literature has also confirmed that EZH2 contributed to accumulation of cells in the S phase while reduced the cell in G1 phase [Bachmann et al, ]. Additionally, the increased cell invasion and migration were related to the down‐regulated E‐cadherin and up‐regulated vimentin [Lee et al, ]. In our experiments, we found that the knockdown of EZH2 by transfecting siRNA‐ EZH2 , the expression of cyclin D1 , NOTCH1 , β‐catenin , and vimentin protein was obviously reduced while that of E‐cadherin protein was promoted compared with the control group.…”
Section: Discussionsupporting
confidence: 72%
“…For cell cycle, the early literature has also confirmed that EZH2 contributed to accumulation of cells in the S phase while reduced the cell in G1 phase [Bachmann et al, ]. Additionally, the increased cell invasion and migration were related to the down‐regulated E‐cadherin and up‐regulated vimentin [Lee et al, ]. In our experiments, we found that the knockdown of EZH2 by transfecting siRNA‐ EZH2 , the expression of cyclin D1 , NOTCH1 , β‐catenin , and vimentin protein was obviously reduced while that of E‐cadherin protein was promoted compared with the control group.…”
Section: Discussionsupporting
confidence: 72%
“…Genistein first isolated from Genista tinctoria can suppress psoriasis-related inflammation through a STAT3/NF-κB-dependent mechanism in keratinocytes [172,173]. For more detailed information about genistein's anti-inflammatory action or anti-EMT, please refer to a previous review by Spagnulo et al and Lee et al [174,175]. Genistein (200 µM) can induce apoptosis of colon cancer cells by reversal of EMT via a notch1/NF-κB/slug/E-cadherin pathway [176].…”
Section: Reversal Of Emt By Anti-inflammatory Natural Compoundsmentioning
confidence: 99%
“…In frogs and rats, genistein alters thyroid hormone signaling and thyroid morphology and reduces thyroid hormone receptor transcription (Ji et al., ; Sosić‐Jurjević et al., ). In cancer models, genistein limits metastasis by inhibiting Notch‐1 and TGF‐beta signaling and promoting tumor cell apoptosis (Lee, Hwang, & Choi, ; Liu‐Smith & Meyskens, ). It is remarkable that one molecule can influence physiological function in plants and animals through such diverse mechanisms with a variety of outcomes.…”
Section: Hap Effects On Vertebratesmentioning
confidence: 99%
“…Interestingly, closely related species can exhibit different levels of receptor activation by HAPs, as shown for southern white rhinoceros and one‐horned rhinoceros (Tubbs, Hartig, Cardon, Varga, & Milnes, ). HAPs also participate in nongenomic signaling pathways that alter phosphorylation reactions, enzymatic activity, and second messenger cascades (Greathouse et al., ; Lee et al., ). A recent survey of eleven plant species in Uganda found that extracts of leaves, bark, or flowers showed varying degrees of receptor binding in estradiol, progesterone, androgen, and cortisol assays (Wasserman et al., ).…”
Section: Hap Effects On Vertebratesmentioning
confidence: 99%